2013
DOI: 10.5901/jesr.2013.v3n3p79
|View full text |Cite
|
Sign up to set email alerts
|

Graduate Students’ Perception of the Design and Management of Graduate Programs: A Case Study of Egerton University

Abstract: This study was designed to provide information on the quality of educational programs as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…Classrooms rated the highest implementation, followed by faculty members, library and administration, respectively. These results are matching with Lopokoiyit and Chepkilot (2013) stated in Egerton University, program quality rated 69.6 per cent, administrative staff quality 72.5 per cent and faculty staff quality 62.5 per cent. Mansoor and Ali (2015) said in Sri Lankan universities that students' satisfaction on their academic performance quality was 3.29.…”
Section: Results Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Classrooms rated the highest implementation, followed by faculty members, library and administration, respectively. These results are matching with Lopokoiyit and Chepkilot (2013) stated in Egerton University, program quality rated 69.6 per cent, administrative staff quality 72.5 per cent and faculty staff quality 62.5 per cent. Mansoor and Ali (2015) said in Sri Lankan universities that students' satisfaction on their academic performance quality was 3.29.…”
Section: Results Discussionsupporting
confidence: 88%
“…Business education graduates need to possess teamwork competencies, which are necessary for the marketplace (Oduma and Ile, 2012). In Egerton University, program quality rated 69.6 per cent, administrative staff quality rated 72.5 per cent, faculty staff quality rated 62.5 per cent, and all were affecting graduates' satisfaction (Lopokoiyit and Chepkilot, 2013). A survey that included 47,342 graduates from the Italian National Statistical Institute confirmed that participating in university activities with sustainable academic performance increases the possibility of employment (Ciriaci and Muscio, 2014).…”
Section: Qae 273mentioning
confidence: 95%
See 1 more Smart Citation